Production gains in cost-effectiveness analyses: a welfare-theoretical approach - Bodil O. Hansen; Hans keiding (Copenhagen Business School (CBS), Department of Economics, 1999)
In the literature on cost-effectiveness analyses, there has recently been considerable debate on the way of measuring the production gain caused by a new treatment as well as its proper evaluation. In this paper, we propose a general framework for the discussion of such questions in the form of a general equilibrium model with separate health variables. It is shown how the standard methods of cost-effectiveness and cost-utility analysis are derived from basic assumptions. Also, the question of whether to choose the human capital or the frictional method in evaluating production gains can be given an answer in this model.
hdl:10398/7489
Keywords: D61; 330; Cost-effectiveness analysis; Production gain; General equilibrium model; Health variables; Cost-utility analysis